PERBANDINGAN KEMAMPUAN KOMUNIKASI MATEMATIS MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DENGAN REALISTIC MATHEMATICS EDUCATION SISWA KELAS VI SEKOLAH DASAR KABUPATEN SIJUNJUNG - Samariady, Zulfi; Arifmiboy; Malta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low mathematical abilities of students in mathematics subjects. This can be seen from the low scores obtained by students, especially in mathematical communication skills. The low results of students' mathematical communication cannot be separated from the approach taken by the teacher. There are a number of approaches that can improve students' mathematical communication skills, including the Contextual Teaching and Learning (CTL) approach and the Realistic Mathematics Education (RME) approach. However, in this case the author cannot be sure which approach is better. Therefore, the aim of this research is to compare mathematical communication skills using Contextual Teaching and Learning with Realistic Mathematics Education of Class VI Elementary School Students in Sijunjung Regency. This research is a quasi-experimental research with a non-equivalent pretest-posttest control group research design. The data analysis process used in this research uses a 2x2 Factorial Design with the static group comparison design. From data analysis and hypotheses it was found that (1) there was a significant influence of using the Contextual Teaching and Learning (CTL) approach on the mathematical communication skills of class VI students at SDN 28 Padang Laweh. (2) there is a significant effect of using the Realistic Mathematics Educaton (RME) approach on the mathematical communication skills of class VI students at SDN 20 Padang Laweh. (3) there is a significant difference in students' mathematical communication abilities using the Contextual Teaching and Learning approach with the Realistic Mathematics Educaton (RME) Approach in class VI at SD Negeri 28 Padang Laweh and at SD Negeri 20 Padang Laweh